Osimertinib a new weapon in epidermal growth factor receptor-mutated non-small cell lung cancer patients - Rossi, Antonio (Translational Cancer Research; Vol 6, Supplement 3 (May 26, 2017): Translational Cancer Research, 2017)
Non-small-cell lung cancer (NSCLC) accounts for about 85% of all new lung cancer diagnoses every year worldwide (1). Unfortunately, in most cases the diagnosis is made when the disease is already in a metastatic stage with the systemic therapy being the standard-of-care. In approximatively 20% of Caucasian NSCLC patients (2), and in about 50% of Eastern Asian ones (3), an oncogene-addicted NSCLC is diagnosed, due to the presence of epidermal growth factor receptor (EGFR) activating mutations or anaplastic lymphoma kinase (ALK) and proto-oncogene tyrosine-protein kinase ROS (ROS1) rearrangements. These gene alterations identify patients who benefit from the use of correspondent inhibitors (4,5).